Adamastoraltica humicola, new genus and new species: the first example of possible moss-inhabiting flea beetle genus from sub-Saharan Africa (Coleoptera, Chrysomelidae, Galerucinae) - Biondi, Maurizio; Iannella, Mattia; D’alessandro, Paola (Zootaxa, 2020)
Adamastoraltica humicola gen. nov. and sp. nov. from the Republic of South Africa (Western Cape Province) is described. The new genus, collected in the humus, shows external characteristics typical of the moss-inhabiting flea beetle genera, mainly: very small size, very convex and subglobose body, antennae with enlarged apical antennomeres, strongly reduced hind wings, greatly simplified and shortened mesothorax and metathorax, and elytra lacking humeral calli. Adamastoraltica gen. nov. shows some similarities with the Asian genus Cangshanaltica Konstantinov, Chamorro, Prathapan, Ge & Yang. However, the absence of the scutellum brings this new genus close to Stegnaspea Baly, also occurring in Western Cape Province. For the new flea beetle genus, data on distribution are supplied, along with preliminary ecological notes. Photomicrographs of main morphological characters, including male and female genitalia, and metafemoral extensor tendon are also provided. Finally, the updated distribution of the moss-inhabiting flea beetle genera described so far, excluding the subtribe Monoplatina, is supplied.